2021
DOI: 10.1371/journal.pone.0250547
|View full text |Cite
|
Sign up to set email alerts
|

Fear of pain moderates the relationship between self-reported fatigue and methionine allele of catechol-O-methyltransferase gene in patients with fibromyalgia

Abstract: Previous research has shown a consistent association among genetic factors, psychological symptoms and pain associated with fibromyalgia. However, how these symptoms interact to moderate genetic factors in fibromyalgia has rarely been studied to date. The present research investigates whether psychological symptoms can moderate the effects of catechol-O-methyltransferase on pain and fatigue. A total of 108 women diagnosed with fibromyalgia and 77 healthy control participants took part in the study. Pain, fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…Beyond widespread pain, patients commonly have additional physical, affective and cognitive alterations (Aparicio et al, 2013;Bell et al, 2018;Ferrera et al, 2021;Mercado et al, 2022). Indeed, current evidence has confirmed the principal role of attentional and affective processes in influencing pain hypersensitivity in fibromyalgia (Peters et al, 2000;Gracely et al, 2002;Geisser et al, 2003;Giesecke et al, 2005;Bartley et al, 2009;Duschek et al, 2014;Ellingson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond widespread pain, patients commonly have additional physical, affective and cognitive alterations (Aparicio et al, 2013;Bell et al, 2018;Ferrera et al, 2021;Mercado et al, 2022). Indeed, current evidence has confirmed the principal role of attentional and affective processes in influencing pain hypersensitivity in fibromyalgia (Peters et al, 2000;Gracely et al, 2002;Geisser et al, 2003;Giesecke et al, 2005;Bartley et al, 2009;Duschek et al, 2014;Ellingson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Catechol-O-methyltransferase (COMT) gene is one of the possible candidates associated, at least partially, with interindividual variability in physical, psychological or cognitive symptoms in fibromyalgia [3,[19][20][21][22][23][24]. This gene encodes an enzyme of the same name, which is involved in the degradation of catecholamines, such as dopamine, adrenaline or noradrenaline [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The Met/Met genotype is associated with three to four times lower activity of the COMT enzyme than Val/Val genotype [32], whereas Met/Val seems to have intermediate levels of enzyme activity [33]. Briefly, the Met/ Met genotype of the Val158Met polymorphism has been associated with an increase in tender points [19][20][21][22], the severity of fatigue [3], and depression or anxiety symptomatology in fibromyalgia [23,34]. Complementarily, recent findings regarding cognitive impairment have indicated that patients with fibromyalgia bearing the Val/Val genotype showed a worsening in working memory tasks compared to healthy control participants carrying the same genotype [24].…”
Section: Introductionmentioning
confidence: 99%
“…By regulating the dopaminergic pathways, COMT participates in the opioidergic central processing of pain [ 3 ]. A relationship between methionine alleles of the COMT gene and fatigue has even been suggested, which could be moderated by different levels of fear of pain, establishing an association between psychological and physical factors [ 4 ]. Among Spanish women with FM, an early study found an association between rs4818 polymorphism and self-reported pain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%